Serum Zinc and Copper Changes in Male Infertility - ibrahim, Hadee (Iraqi National Journal of Nursing Specialties, 2013)
Objective: The aim of this study to detect the correlation between trace elements such as zinc, copper andspermatogenesis, sperm viability and motility.Methodology: Serum and semen samples were collected from one hundred twenty patients with age ranged (20-50 years) attending the high institute for Embryo Research and Infertility Treatment/ Baghdad University, inaddition to thirty fertile males their age comparable to that of patients. The period of this study was from June2004 until the end of October 2004.Results: The result of routine seminal fluid analysis of all infertile males was divided according to WHO, (1999) limitinto four groups: Asthenospermia(A), Asthenoteratospermia(AT), Oligoasthenoteratospermia OAT andAzoospermia(Azoo), each group includes thirty patient. Results showed highly significant decrease in serum zincconcentration in different infertile groups compared to control group, and a slight increase in serum copperconcentration in different infertile group. With advancing age, all the infertile groups, as well as the control group,had a slight decrease in serum concentration of zinc, and a slight increase in serum copper concentration.Recommendations: Further studies are needed to evaluate the levels of different biochemical parameters inseminal plasma of different infertile groups.